Astronomy and Cosmology in research: a bibliometric analysis: un análisis bibliométrico - Xavier, Lucas Antonio; Rodrigues, Chirlei de Fátima; Fardim , Simone Vieira Sant’Anna (Cadernos de Astronomia, 2023)
"Cadernos de Astronomia" is a periodical publication dedicated to scientific dissemination, the history of science, teaching and research in astronomy and related areas. Aimed at serving a wide audience, the magazine focuses on scientific knowledge related to astronomy, cosmology and gravitation. In this study, with a qualitative bias, we sought to analyze the journal’s publications in a specific period of time. To carry out a systematic review, six different categories of articles were adopted. To approximate the way in which scientists have been producing their results, two databases, Scopus and Web of Science, were accessed. The "Primordial Universe" was considered as a research topic in these databases. After the analysis of the selected articles, it was possible to reflect on the importance of scientific communities for the continuity of the development of scientific research. Since the teaching of astronomy has been integrated into the secondary school curriculum from 2022, it is believed that the scientific output of the journal has great potential to assisting teachers in their pedagogical practices.